PENGARUH PENERAPAN STRATEGI KEUNGGULAN BERSAING DAN TOTAL QUALITY MANAGEMENT TERHADAP KINERJA PERUSAHAAN DENGAN INFORMASI AKUNTANSI MANAJEMEN SEBAGAI VARIABEL MODERATING (Studi pada BUMN Industri Strategis di Kota Bandung) - Angela Merici Minggu (Akademi Akuntansi YKPN Yogyakarta, 2014)
This study aim to estimate empirically the influence of competitive advantage strategy and total quality management implementation simultaneously or partialy on BUMN-IS performance in Bandung with management accounting information as a moderating variable. The method uses in this research is census method. In determining the number of samples, because the subject is less than a hundred, taken all the better The researh conducted on 55 manager on BUMN strategic industry in Bandung. Data used in this research were primary data collected by questioners. Analysis method uses in this researh was descriptive and verifikatif analisys and hypothesis testing method used MRA (Moderated Regression Analysis). The result of this research show that there are the effect of competitive advantage strategy and implementation of total quality management simultaneously on organization performance. Partially the competitive advantage strategy has a positive influence on organization performance, total quality management whereas no significant influence on organization performance and management accounting information moderate the competitive advantage and TQM has a positive significant influence on organization performance Keywords : competitive advantage strategy, total quality management, management accounting information and organization performance.